PERSEPSI PENGUNJUNG TERHADAP KEBERADAAN PEDAGANG KAKI LIMA DI OBJEK WISATA JAM GADANG BUKITTINGGI - Putra, Bayu Permana; Kasmita, Kasmita; Abrian, Youmil (Journal of Home Economics and Tourism, 2016)
This study aims to determine the visitor's perception of the existence of street vendors in tourism object Jam Gadang Bukittinggi which included 4 of 7 indicators stepping, namely: a safe, orderly, clean and friendly. This type of research is descriptive research with survey method. The study population amounted 38.795 people. The sampling method is non-probability sampling, by incidental technique. The research sample of 100 people. Data collection techniques using a questionnaire with a Likert scale that has been tested for validity and reliability. Data were analyzed through descriptive analysis categorizing method of assessment based on the average scores and percentage assessment. The study concluded that the general perception of visitors to the existence of street vendors in tourism object Jam Gadang Bukittinggi 56% said either. While based on each of the indicators are: (1) Safe 53% said good, (2) Orderly 37% said either, (3) Clean 58% said very good, (4 ) Friendly 59% said either.1